An Iranian childhood rethinking history and memory - Dabashi, Hamid 1951- (Cambridge University Press, 2023)
Hamid Dabashi was born and raised in southern Iran in the 1950s and 1960s. During this time, his homeland was changed beyond recognition, from the 1953 coup d'état to the 1963 political protests and the beginning of the Marxist rebellions against the Shah in 1971. In this vibrant, unique and personal study, Dabashi recounts his experience of this defining period in modern Iranian history, deftly blending the personal with the political, the ordinary with the extraordinary. Lyrically written, he combines vivid childhood memories with careful reflection to explore the intersection of history and memory. The book draws upon a rich tapestry of themes and sources, including art, literature, and folklore. In doing so, Dabashi asserts the power and place of the knowing postcolonial subject. Redrawing the limits of modern literary historiography, he asks what it means to be a Muslim and an Iranian, and, indeed, what it is that forms the humanity of a person
Title from publisher's bibliographic system (viewed on 13 Apr 2023)
Myself as Another -- My Memories of our Forgetfulness -- Once Upon a Moonlight in the Merry Month of June -- The House in the Ardeshir Street -- My Elephant was Dreaming of India -- Myself as Myself
Keywords: Dabashi, Hamid / 1951- / Childhood and youth; Dabashi, Hamid / 1951- / Books and reading; Muslim children / Iran / Ahvāz / Biography; Iranian Americans / New York (State) / New York / Biography; Ahvāz (Iran) / Biography; Ahvāz (Iran) / Social life and customs / 20th century; Iran / Politics and government / 1925-1979